PKM PENGOLAHAN IKAN BANDENG MENJADI LONTONG ISI ABON BANDENG MAKANAN KHAS SAWAH LUHUR - Doni Pernanda; Sanjaya Sanjaya; Nita Afrillia; Jelita Nada Fairuz; Salsa Nabila (Yayasan Education and Social Center, 2021)
Sawah Luhur Village, which is located in Kasemen District, Serang City, Banten Province, is an area of rice fields and fish ponds that have considerable potential, especially in the aquaculture sector. Pond products are the main source of livelihood for the majority of the population. Milkfish is one of the large fishery products, but not only milkfish is processed into milkfish pecak and milkfish satay, but it can also be processed into rice cake containing shredded milkfish. With the potential for milkfish ponds, the Uniba Group 05 Student PKM program utilizes milkfish processing into lontong containing shredded milkfish. It is hoped that this processing can continue and be continued by the community so that it becomes a business area that can improve the family's economy, supported by online-based marketing in the midst of the COVID-19 pandemic which has not yet moved from Indonesia. . This research is a development research. The milkfish processing model in this study was adapted from a 4-D model development model consisting of define, design, develop, and disseminate stages. The trial was carried out in three stages, namely (1) expert trial/validation; (2) limited trial; and (3) field trials. Field trials were carried out in the Sawah Sawah Luhur sub-district. The research instrument used was a field survey of fish ponds from milkfish processing into lontong containing shredded milkfish. This field observation is about the processing of milkfish, the achievement of milkfish into processed lontong. Our achievements in processing lontong fish have been successful. Each component of the learning device for making shredded milkfish in Sawah Luhur has met the valid criteria